Diasporan students social entrepreneurship intention: The moderating role of institutional support. Issue 1 (8th July 2020) - Lukman, Sadia; Bao, Peng Xiao; Kweku‐Lugu, Benjamin; Arkorful, Vincent Ekow; Latif, Amadu; Gadabu, Annabelle; Charmaine‐Kwade, Priscilla; Basiru, Ibrahim; Sadiq, Mohammed Abubakar
Abstract : The daunting global challenges saddling polities and governments alike have resultantly created a situation whereby governments and corporate civil society have inadvertently reneged on delivering public good and services to citizens. In ensuring and strengthening a public–private actor synergy, with particular emphasis on leveraging acquired knowledge and skills of diaspora‐based students, social entrepreneurship activities could be harnessed to provide sustainable remedies to social challenges such as unemployment, famine amongst others by utilizing social entrepreneurship as a tool. Using the theory of planned behaviour as a theoretical framework, the study elicited data from 322 respondents to empirically investigate determinants of social entrepreneurship intentions of Ghanaian students, with the moderating role of institutional support. Study results revealed that sense of social responsibility and service learning have significant relationship with social entrepreneurship intention. However, social volunteering experience had no significant relationship. Moreover, whereas attitude to social entrepreneurship intention demonstrated a positive relationship, institutional support as a moderator was also revealed to influence the relationship between attitude and social entrepreneurship intention. From the study findings, we discourse on the implications for social entrepreneurship in Ghana to policy makers and stakeholders.